169 Developing capture assays to measure circulating crp/oxidised low density lipoprotein complexes in patients undergoing cardiopulmonary bypass and examining use of crp/oxidised low density lipoprotein complexes as a biomarker of atherosclerosis. (5th June 2017) - Mann, Prachi; Khamis, Ramzi YJ; Haskard, Dorian; Ta, Minh; Kojima, Chiari; Ammari, Tareq; Caga-Anan, Mikhail; Nguyen, Bao A; Anderson, Jonathan R; Evans, Paul C; Johns, Michael
Abstract : Background: Atherosclerosis is a disease of global importance. It is a systemic chronic inflammatory disease with a complex aetiology. LDL is primarily oxidised in the subendothelial space, as plasma antioxidants protect circulating LDL from oxidation. However, small amounts of oxidised LDL (oxLDL) have been detected in plasma. Modified LDL is thought to circulate as part of an immune complex; these immune complexes may also include CRP, complement and IgM antibodies. This project aims to develop a capture ELISA to measure oxLDL/CRP complexes in circulation, to help better characterise circulating immune complexes and explore potential use of oxLDL/CRP complexes a biomarker of atherosclerosis. Methods: A CRP/oxLDL capture ELISA was developed using LO1, a novel mAb specific to oxLDL. Plasma samples were obtained from patients undergoing cardiopulmonary bypass at four different timepoints. Levels of oxLDL, CRP and oxLDL/CRP complexes were determined in patient plasma using capture assays developed during this study. Results: OxLDL levels show an uptrend from baseline to 60mins, followed by significant reduction at 300mins compared to baseline (0.506±0.078 vs 0.456±0.035; p=0.0138). CRP concentration initially declines from baseline up to 120mins (1.918±0.915 vs 1.136±0.599; p=0.0009), after which levels rise between 120 min and 300 min (1.136±0.599 vs 1.782±0.65; p=0.0026). There is no significant difference in levels of CRP/oxLDL complexes across all timepoints. Conclusion: It is possible to measure CRP/oxLDL complexes in plasma. Pro-inflammatory events such as cardiopulmonary bypass are associated with changes in levels of oxLDL and CRP, while oxLDL/CRP levels remain unchanged.